The potentials of novel native fungi in delignification of lignocellulose biomass wastes - Farouq, Ahmadu Ali; Abdullah, Dzulkefly Kuang (Planetary Scientific Research Center, 2014)
The potentials of two new native fungi Trichoderma aureoviride UPM 09 JN811061 and Fusarium equiseti UPM 09 JN811063 isolated from Asian elephant dung for their ability to digest lignin and hemicellulose was exploited using two pretreatment methods, submerged cultivation (SMC) and solid state cultivation (SSC). The pretreatment effect (% loss on lignin and hemicellulose determined after treatment) on rice husk (RH), rubber wood saw dust (RW) and oil palm empty fruit bunch (EFB) using SMC and SSC by T. aureoviride UPM 09 JN811061 was statistically significantly (P<0.05) higher than by F. equiseti UPM 09 JN811063. However, the result of this study, therefore, showed that the fungi T. aureoviride UPM 09 JN811061 and F. equiseti UPM 09 JN811063 both have great selectivity for lignin with T. aureoviride UPM 09 JN811061 having greater selectivity.